C.3 - Dasgupta,Supriya (Bangalore, 1988)
The need was felt of working for a women's organisation among the tribals because our earlier studies had shown that deforestation caused by industry had resulted in the deterioration of the status of all tribals. But the status of their women had deteriorated more than that of their men. The destruction of forests which were their very life support system has resulted in the total destabilisation of their community. The effects were bound to be felt by women more than by men, because tribal and forest economy is essentially a women's economy. In this booklet we study the nature of this economy, the extent of deforestation and its consequences on women. Some solutions are suggested with the hope of contributing to the empowerment of a group that has been further marginalised by the present pattern of development.
Keywords: Women Social conditions